Analysis of Women’s Representation in Politics And Human Rights Based on Islamic Gender Equality Perspective - Fitria Rizky Maharani; Fita Nurotul Faizah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2021)
This article aims to explain the legal guarantees regarding women's involvement in politics. The involvement of women in politics is very important to voice women’s rights and concerns and to find some efforts that can realize gender equality, especially in the political field. By applying the normative approach method or library research, the writer will analyze the women’s representation in politics and human rights based on islamic gender equality perspective. This research finds that there is a law allowing women’s position in politics, but it has not been optimally applied. In addition, the writer also finds that there is discrimination experienced by women that has impacts on human rights injustice.